Dynamic of seismic noise sources in the Mediterranean Sea: implication for monitoring using noise correlations - Stehly, Laurent; Delouche, Estelle; Tomasetto, Lisa; Ranjan, Pratul (Comptes Rendus. Géoscience)
We study the dynamics of short-period (1–3 s) seismic noise across Europe and its implication on the convergence speed of noise auto-correlation coda waves. Our aim is not to describe the source of the seismic noise with high spatial resolution, since this has already been done by a number of previous studies. Instead, the goal of this work is to study how the dynamics of the seismic noise affect the possibility of monitoring the evolution of the crust, in particular the temporal resolution and accuracy of the velocity change that can be detected.To that end, we perform a single station analysis at all available European broadband stations in 2021 using a proxy that quantifies the extent to which the frequency content of the noise wavefield is stationary over time, independently of its amplitude variations. We show that at short periods (${<}$3 s), the noise field in Europe is dominated by surface waves coming from the north Atlantic ocean, with also a significant contribution from the Adriatic and Aegean Seas in southern Europe. The relative contribution of these two source regions depends on the season, with the influence of the Adriatic and Aegean Sea increasing in summer.The interplay of these two sources regions creates lateral variations in the properties of the seismic noise. Thus, the noise field is more stable in northern Europe where the influence of the Atlantic Ocean predominates, while along the Adriatic coast and around the Aegean Sea, micro-seismic events lasting several hours are regularly detected, especially in summer. This leads to strong lateral variation in the convergence velocity of the coda waves, and thus in the accuracy and temporal resolution of the velocity changes that can be detected in Europe.